Finance and technology. Trends that determine the development and transformation of banking business - Aleksandrov , A. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2023)
The article is dedicated to analyzing contemporary changes in the banking business that have occurred since the forced isolation caused by the COVID-19 pandemic. The pandemic rapidly triggered the most extensive transformation in banking technology, client-bank communication, and the emergence of new opportunities driven by digital financial services. The drivers of new services (embedded finance, Buy Now Pay Later (BNPL)) are the Millennials and Generation Z. Cybersecurity risks and digital financial fraud have significantly increased. There is a need for competence growth of skills among both bank employees and clients. A fundamental question has arisen regarding the balance between the use of digital technologies and human involvement in the banking business, leading to a broad expert and academic dialogue (the Phygital challenge). The pandemic also impacted the macroeconomic situation in the global economy. The need for support for the population and small to medium-sized businesses led governments to resort to issuance. The consequences were economic imbalances and inflation growth in leading economies. However, measures to counter inflation and stabilize the economy resulted in an increase in interest rates in the U.S. and the EU, as the world’s leading economies. This allows a return to traditional banking practices and a reassessment of interactions with FinTech solutions. The major changes analysis helps to identify the most significant trends influencing modern banking, thereby allowing the forecasting of the development dynamics of the situation.